PENERAPAN SISTEM BAGI HASIL PADA TANAMAN JERUK DESA KEBONDALEM KECAMATAN BANGOREJO KABUPATEN BANYUWANGI - Jamaluddin, Cinta (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2024)
This research aims to determine the profit sharing system for orange crops in Kebondalem Village, District Bangorejo Banyuwangi Regency and to explain the social relations of farmer owners and farmers cultivators in the citrus crop sharing system in Kebondalem Village, Bangorejo District, Regency Banyuwangi. The research subjects are orange farmers who own it and the cultivators who share it The results were 325 people and the research informants were orange farmers who owned it and the cultivators who carried it out share the profits of maro, mertelu, and dove. The data collection technique is using the observation method participation, in-depth interviews, documents and documentation. The data obtained in this research will qualitative descriptive method was used. The research results show that there are many profit sharing systems used by orange farmers in Kebondalem Village, Bangorejo District, Banyuwangi Regency, namely for Maro and Mertelu results. The people of Kebondalem Village, Bangorejo District, are fulfilling their needs His needs mostly work as a farmer. However, not all farmers have their own land managed, so that many people in Kebondalem Village use a profit sharing system. Profit-sharing system In orange farming, the aim is to show a sense of solidarity between farmers, namely each other help each other and show that humans cannot live alone, but always need other people in all aspects.